Interleukin 35-Producing Exosomes Suppress Neuroinflammation and Autoimmune Uveitis - Kang, Minkyung; Choi, Jin Kyeong; Jittayasothorn, Yingyos; Egwuagu, Charles E. (Frontiers in Immunology, 2020)
Corticosteroids are effective therapy for autoimmune diseases but serious adverse effects preclude their prolonged use. However, immune-suppressive biologics that inhibit lymphoid proliferation are now in use as corticosteroid sparing-agents but with variable success; thus, the need to develop alternative immune-suppressive approaches including cell-based therapies. Efficacy of ex-vivo-generated IL-35-producing regulatory B-cells (i35-Bregs) in suppressing/ameliorating encephalomyelitis or uveitis in mouse models of multiple sclerosis or uveitis, respectively, is therefore a promising therapeutic approach for CNS autoimmune diseases. However, i35-Breg therapy in human uveitis would require producing autologous Bregs from each patient to avoid immune-rejection. Because exosomes exhibit minimal toxicity and immunogenicity, we investigated whether i35-Bregs release exosomes that can be exploited therapeutically. Here, we demonstrate that i35-Bregs release exosomes that contain IL-35 (i35-Exosomes). In this proof-of-concept study, we induced experimental autoimmune uveitis (EAU), monitored EAU progression by fundoscopy, histology, optical coherence tomography and electroretinography and investigated whether i35-Exosomes treatment would suppress uveitis. Mice treated with i35-Exosomes developed mild EAU with low EAU scores and disease protection correlated with expansion of IL-10 and IL-35 secreting Treg cells with concomitant suppression of Th17 responses. In contrast, significant increase of Th17 cells in vitreous and retina of control mouse eyes was accompanied by severe choroiditis, massive retinal-folds and photoreceptor cell damage. These hallmark features of severe uveitis were absent in exosome-treated mice and visual impairment detected by ERG was modest compared to control mice. Absence of toxicity or alloreactivity associated with exosomes thus makes i35-Exosomes attractive therapeutic option for delivering IL-35 into CNS tissues